A Comparative Study of Various Methods Involved in Design of Reinforced Concrete Beams with Web Openings (International Journal of Innovative Research in Engineering & Management, 2022)
A design problem involving design of beam  with an opening has been solved as an explanation for the  different methods. The design of beam with web openings is  done from various methods like plasticity truss method,  plastic hinge method, traditional design approach, IS code  and AIJ method. After the designing part comparisons have  been drawn between the various methods. These  comparisons give a clear idea of the pros and cons of these  methods. MATLAB as well as Microsoft Excel have been  used as a programming tool. It has been concluded that the Plasticity Truss Method  provides a more conservative design approach than the  Plastic Hinge Method. However the plasticity truss method  requires more longitudinal reinforcement in the chord  members as compared to the plastic hinge method. In this  study, It has been calculated reinforcements for two beams  with small opening and large opening respectively, under its  ultimate load, for different longitudinal locations of the  opening and different lengths of opening. The variations in  area of steel have been recorded and explained for variations  in these parameters. Two design methods, Traditional  Design Method and Plasticity Truss Method, have been used  for the beam with small opening, and compared. Beam with  large opening has been designed using Plasticity Truss  Method and ACI 318. This work also presents the comparison of reinforcements obtained in above case using IS456 and ACI 318. The results have been compared through  graphs and possible reasons of difference in results of two  theories have been mentioned. This study shows the  reinforcement detailing required near the opening region of  a beam, which focuses on crack control along with  strengthening beam in flexure and shear.
Keywords: Concrete beam; Mat lab; Plasticity; Truss; Web opening